2016
DOI: 10.1097/md.0000000000003208
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Involvement in Radiologically Isolated Syndrome

Abstract: The unanticipated magnetic resonance imaging (MRI) detection in the brain of asymptomatic subjects of white matter lesions suggestive of multiple sclerosis has recently been named as radiologically isolated syndrome (RIS). The pathophysiological processes of RIS remain largely unknown and questions as to whether gray matter alterations actually occur in this entity are yet to be investigated in more detail. By means of a 3 T multimodal MRI approach, we searched for cortical and deep gray matter changes in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 54 publications
0
18
2
1
Order By: Relevance
“…Diffusion tensor imaging studies, regardless of the analysis method used to determine fractional anisotropy or mean diffusivity measures, have revealed that RIS patients do show altered microstructural white matter integrity with respect to controls but only correspondence of lesions. 29,30 Taken together, these studies strongly suggest that occult microstructural normal-appearing white matter damage is not significantly present outside visible T2 lesions in RIS, suggesting that RIS patients might have experienced more efficient reparative mechanisms after white matter injury.…”
Section: Health-related Quality Of Lifementioning
confidence: 89%
See 1 more Smart Citation
“…Diffusion tensor imaging studies, regardless of the analysis method used to determine fractional anisotropy or mean diffusivity measures, have revealed that RIS patients do show altered microstructural white matter integrity with respect to controls but only correspondence of lesions. 29,30 Taken together, these studies strongly suggest that occult microstructural normal-appearing white matter damage is not significantly present outside visible T2 lesions in RIS, suggesting that RIS patients might have experienced more efficient reparative mechanisms after white matter injury.…”
Section: Health-related Quality Of Lifementioning
confidence: 89%
“…25,30 In addition, we have recently found significant thinning in a number of cortical areas primarily distributed in frontal and temporal lobes, as well as cingulate cortex. 30 Remarkably, we did not observe cortical thickness in those brain regions that have been shown to play a critical role in motor function and physical dysfunction (precentral gyrus, sensorimotor cortex, and cerebellum), which may help explain why RIS patients maintain motor functions. 30 In contrast to our results, Azevedo et al 25 found only a limited area of thinning in the right superior and inferior parietal gyri.…”
Section: Health-related Quality Of Lifementioning
confidence: 98%
“…Gray matter atrophy is found in a gradient with increasing severity in clinically isolated syndrome, RRMS, and SPMS (as compared with healthy controls), while white matter atrophy appears to be relatively constant of the disease course. Mechanisms of direct injury, as well as antegrade and retrograde axonal degeneration, has been hypothesized for the gray matter in MS-even in radiologically isolated syndrome gray matter volume is reduced [33]. Gray matter atrophy demonstrates stronger correlations with cognitive function [34,35].…”
Section: Gray Matter Atrophymentioning
confidence: 99%
“…There is a growing amount of evidence suggesting that RIS and MS patients share both nonmotor clinical features [ 2 5 ] and quantitative brain tissue damage. [ 6 12 ] Accordingly, approximately one-third of RIS subjects, especially those with spinal cord involvement, will present a future demyelinating event within 5 years after diagnosis. [ 13 ] However, to date it remains largely unknown whether there is in RIS brain damage beyond visible T2 white matter lesions.…”
Section: Introductionmentioning
confidence: 99%